2007
DOI: 10.1007/bf03404329
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting Change Over Time in Self-reported Health

Abstract: Background: Self-reported health status has become a conventional measure of health status at the population level. Further, the literature supports its use as a valid indicator of morbidity and mortality. However, relatively little attention has been paid to how selfreported health status changes over time or the factors affecting change. This paper explores the factors affecting health status change over time using data from a neighbourhood health survey. Methods: Two rounds (2001; 2003) of health survey dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 50 publications
0
12
0
Order By: Relevance
“…Thus, only associations between green space and self-rated health at one point in time could be studied. Besides temporal changes of gender roles and sex/gender impacts, especially the self-rated health status could change over time and be influenced by far-reaching experiences such as a divorce or job loss or a change in lifestyle behavior such as quitting smoking or use of health care [52].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, only associations between green space and self-rated health at one point in time could be studied. Besides temporal changes of gender roles and sex/gender impacts, especially the self-rated health status could change over time and be influenced by far-reaching experiences such as a divorce or job loss or a change in lifestyle behavior such as quitting smoking or use of health care [52].…”
Section: Discussionmentioning
confidence: 99%
“…Our findings are consistent with some previous studies, 4 but in sharp contrast to that reported by Wilson et al who reported that there was no significant association between changes in self-reported health status and age or gender. 15 Measures of inequality (absolute inequality (AI) and relative inequality (RI)) were implored in our study. We found a slight increase in both AI and RI between the periods 1999-2000 and 2013-2014 for SRGH; except for gender.…”
Section: Discussionmentioning
confidence: 99%
“…Based on previous studies of child self-rated health and theoretical rationale, child and household socio-demographic characteristics and household SES covariates were used as controls in the analysis (Cagney et al, 2005; Waters et al, 2000; Wilson et al, 2007; {Reference Removed for Review}). Socio-demographic characteristics included child race, child sex, parental health (good health vs. poor health), maternal marital status (married vs. unmarried), insurance status and a cumulative measure of the number of residential moves a child made.…”
Section: Methodsmentioning
confidence: 99%
“…Despite the widespread use of self-rated health measures, little attention has been paid to how SRH changes over time or how neighborhood racial context impacts change in SRH – particularly for children and adolescents (Cagney et al, 2005; Godley et al, 2010; Power et al, 1998; Wilson et al, 2007). An overwhelming majority of research in this area has examined self-rated health in older populations or populations going through life changes (e.g., menopause), resulting in a large gap in the literature regarding children and adolescents (Browning et al, 2003; Cagney et al, 2005; Godley et al, 2010; Wilson et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation